Coumarins, Fatty Acids, Volatile and Non-volatile Terpenoids from the Leaves of Citrus aurantium L. (Sour Orange) and Citrus sinensis (L.) Osbeck (Sweet Orange) - G., E.; Mahmoud, I.I.; Abou-Moustafa, E.A.; Mabry, T.J. (Asian Journal of Chemistry, 2010)
Coumarins including psoralens were isolated and identified from the leaves of Citrus aurantium var. amara L. (sour orange) and Citrus sinensis L. Osbeck (sweet orange). Five coumarins (aurapten, auraptene, limettin, umbelliferone and osthol) and two coumarins of the psoralen type (bergapten and bergaptol) were obtained from the leaf extract of sour orange while only bergaptol was extracted from the leaf extract of the sweet orange. Although these compounds were previously isolated from roots and fruit peels, this is the first report of these coumarins from the leaves of either species. Twenty six terpenoids plus apiol were obtained from the volatile and non-volatile residues of the extracts, and four of these constituents, apiole, stigmasterol, β-sitosterol and friedelin are reported here to be isolated for the first time from the leaves of these citrus species. Five fatty acids were obtained from the leaves, linoleic, oleic, linolenic, palmitic and palmitoleic and the first two are the major constituents.